IMPLEMENTASI KEBIJAKAN SISTEM TRANSPORTASI DARAT DAN DAMPAKNYA TERHADAP KESEJAHTERAAN SOSIAL DI JAKARTA - Kadarisman, Muh; Gunawan, Aang; Ismiyati, Ismiyati (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2015)
Transportation is the backbone in creating social welfare in Jakarta. Therefore, if there are problems in the transportation system, it will have an impact on the smooth traffic flow and will ultimately hamper the achievement of public welfare. This study used a descriptive-qualitative method. This study refers to the theory proposed by Anderson (in Tachjan, 2006: 23) and Sarana, et al (2009: 9). The results of the study are as follows. Policy implementation transportation system in Jakarta has been able to improve the social welfare of most citizens, which means some people have to feel and enjoy the outcome of transportation development in Jakarta. However, others have not optimally felt the positive impact of the policy. Even, it is perceived negatively; such as traffic jams which are almost evenly distributed throughout Jakarta causing high air pollution, hampered economic activity and generated high economic costs that social welfare was also weakened. This is reinforced by the increasing poverty rate in 2014 that reached 393,980 people thousand compared to previous years.